INVESTIGATING THE ADHERENCE TO THE 5-MINUTE RESTING INSTRUCTION BEFORE SELF-MEASURING HOME BLOOD PRESSURE USING ACCELEROMETER-BASED PHYSICAL ACTIVITY DATA. (April 2021) - de Heus, Rianne; Maasakkers, Carlijn; Claassen, Jurgen
Abstract : Objective: Accuracy of blood pressure (BP) readings is crucial, especially in populations at risk for improper treatment decisions such as older persons. International guidelines recommend 5-minutes rest before taking an office BP measurement and have adopted similar recommendations for home BP measurements (HBPM). However, there is no data underlying this recommendation. Also, it is unknown if patients adhere to this instruction and how non-adherence affects BP. This study addresses these questions in an older population. Design and method: We included 45 patients referred to our geriatric outpatient clinic. HBPM was performed with the memory-equipped Microlife WatchBP home according to guidelines (one week, twice in the morning and twice in the evening), resulting in a max. of 28 measurements per patient. Patients received oral and written instruction to rest at least 5-minutes before taking their BP. During the same week, all patients wore the ActivPAL monitor for 24-hours/day. This is a validated thigh-worn accelerometer able to distinguish between sitting, standing and stepping. Information on physical activity in the 15-minute window before each BP measurement was extracted. In this preliminary analysis we present results from the first 14 patients. Results: These first 14 patients (out of 45) had a mean age of 74.9 ± 10.6 (range: 51–91 years), a mean home BP 146/81 ± 16/12 mmHg and 4 were female. On average, patients adhered to the 5-minute resting instruction in only 22 ± 14% of the measurements (range: 0–50%). Mean resting time was 2.3 ± 2.4 minutes (range: 0–12 minutes). Adherence to the 5-minute resting instruction resulted in significantly lower systolic BP value's compared to non-adherence (143.9 ± 15.4 versus 138.1 ± 14.2 mmHg, p = 0.04) using paired samples t-test. For diastolic BP, the same trend was observed (79.5 ± 7.6 versus 77.6 ± 7.4 mmHg, p = 0.22). Conclusions: These preliminary findings indicate that the instruction to wait 5-minutes before measuring BP at home is often not followed in practice and affects BP value's. Analyses of the full study population will be available at the conference. Since out-of-office BP measurements are becoming more common, these results will provide relevant information on the interpretation of home BP readings.